Atmospheric horizontal extinction determined with a single digital camera-based system in the scope of solar power tower plants. (January 2020) - Barbero, F.J.; Alonso-Montesinos, J.; Ballestrín, J.; Carra, M.E.; Fernández-Reche, J.
Highlights: Horizontal solar radiation attenuation determined with a single digital camera. Application conditioned to have a cloudless sky around a black target. Results similar to those obtained with a two-camera system. Useful in the field of a solar power tower plant. Abstract: A methodology based on the use of a single digital camera has been developed to determine the horizontal attenuation of solar radiation between the field of heliostats and the receiver in a solar tower plant. For this purpose, only the measurement of ambient light and a dark object at known distance is needed. The scenario for this work has been the Plataforma Solar de Almería (PSA, SE Spain), where a large black surface is available. This surface has been designed to be used for a horizontal attenuation measurement system, developed and implemented at the PSA, which is based on the use of two identical digital cameras. Specifically, the horizontal atmospheric attenuation values provided from the single camera-based system and the two camera-based system were compared during several days of July 2018, in conditions of medium values of atmospheric turbidity. A good agreement between the attenuation values obtained with both methods, within their respective uncertainty margins, has been found.